Relationships on operation, human capital management (HCM) and layout of warehouse efficiency in small and medium enterprises (SMEs): Mediating effect of management informations system (MIS) - Mohd Saifudin, Adam; Abdullah, Haim Hilman; Saud, Mohammad Basir (Dalian, China, 2011)
Due to the globalize business, the warehouse activities are now becoming the centre of important to ensure the effective receiving, storing and handling of goods and materials efficiently in the manufacturing firms. Thus it creates the pivotal roles of logistics support in exporting the goods to other destination as excellent hubs with accurate information of timely delivery, receiving of materials and goods through efficient MIS networking. This paper focuses on the warehouse efficiencies based on its operations, layout and Human Capital Management (HCM) in SMEs manufacturing firms and its mediatirg effect with Management information System (MIS). It discusses the introduction and process of warehouse in logistics and supply chain activities, the roles of SMEs, the research and objectives questions, literature review, framework, methodology, hypotheses and results of the research. Lastly it would discuss the conclusion, contribution and-future study of the research.